PENGGUNAAN MEDIA KONKRET UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA MATERI TANAMAN OBAT DI SDN PERCOBAAN 1 MALANG - Wahyu Ezy Asmi Hasanah; Lilik Bintartik; Dwi Ana Lestari; Wahyu Ezy Asmi Hasanah; Lilik Bintartik; Dwi Ana Lestari (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
The quality of learning needs to be improved continuously to optimize the development of learners' skills, knowledge, and attitudes. One effective method is using concrete media to help teachers facilitate learning. Concrete media was used to teach medicinal plant material in class VB. The learning process followed the lesson study flow, consisting of the plan, do & see, and reflection stages. Learning was conducted in two cycles. The first cycle discussed medicinal plants from rhizomes, including ginger, turmeric, kencur, galangal, ginseng, and temulawak. The second cycle covered medicinal plants from leaves, such as bay leaves, lemongrass, guava leaves, cat whisker leaves, basil leaves, betel leaves, celery, kenikir, aloe vera, cinnamon, and pandan leaves. As a result, students' learning motivation increased from 50% before using concrete objects to an average of 80%. Knowledge learning outcomes also improved, rising from an average of 54% to 78%. Additionally, learners' curiosity developed, as evidenced by the variety of questions that arose from students during the learning process. Thus, it can be concluded that using concrete media to teach medicinal plant material can increase the motivation and learning outcomes of fifth-grade students at SDN Percobaan 1.